Dynamic analysis of satellite separation considering the flexibility of interface rings. (August 2015) - Cui, Delin; Yan, Shaoze; Li, Junlan; Qin, Zhaoye; Guo, Xiaosong
Dynamic characteristics of satellite separation are synthetical results of various influencing factors. The improvement of research methods for designing and analyzing the separation system is of great importance for optimizing the dynamic performance of satellite separation. However, there is lack of an integrated approach for studying the satellite separation dynamics with full consideration of the attitude dynamics of satellites, the dynamic envelope of clamp band and the separation shock responses. This paper proposes a modeling and simulation method for comprehensively predicting the dynamic characteristics of satellite separation with the consideration of the flexibility of interface rings. A contrastive analysis of separation dynamics is carried out to determine the effects of the flexible interface rings on satellite separation dynamic characteristics. Subsequently, parametric studies on dynamics of satellite separation are performed, and research emphasis is placed on investigating the effects of position relative to the separation plane, the preload of clamp band, the friction coefficient and the pyroshock of explosive bolts on separation shock responses. The research method proposed in this paper provides a reference for the initial engineering design of the clamp band joint of satellite separation system.